Pengaruh Disiplin Kerja Dan Lingkungan Kerja Terhadap Kinerja Pegawai Pada Dinas Pemuda Dan Olahraga Bengkulu Selatan - Hilen Albert; Siti Hanila; Abdul Rahman (Jurnal Multidisiplin Dehasen (MUDE), 2023)
The purpose of this study is to examine whether there is an effect of work discipline and work environment on employee performance at Youth and Sports Department of South Bengkulu. This research includes quantitative research. This research is categorized as a survey, where the research instrument is a questionnaire. The population and sample in this study were all employees at Youth and Sports Department of South Bengkulu, namely 40 people. The instrument test in this study was carried out using validity and reliability. The data analysis technique in this study used multiple linear regression analysis techniques. The results showed that: (1) work discipline had a positive and significant effect on employees performance at Youth and Sports Department of South Bengkulu (β = 0.343 with a significance level of 0.001); (2) the work environment has a positive and significant effect on the employees performance at Youth and Sports Department of South Bengkulu (β = 0.471 with a significance level of 0.000); (3) Work discipline and work environment have a positive and significant effect on employees performance at Youth and Sports Department of South Bengkulu, which is shown from the results of the regression test that the independent variable greatly influences the dependent variable with a value of 10.058 and work discipline = 0.208 with a significance level of 0.001 and work environment =401 with a significance level of 0.000).